Knowledge, attitudes and behavior regarding topical corticosteroids in a sample of pharmacy students: A cross sectional survey - Karalikkattil T Ashique; Feroze Kaliyadan; Shilpa Mohan; Shreya Vijayan; Dilip Chandrasekhar (Wolters Kluwer Medknow Publications, 2018)
Introduction and Background: The abuse and misuse of topical corticosteroids, especially over the face, is an increasing problem encountered by dermatologists in India. Lack of patient awareness and the ease of obtaining topical corticosteroids without a prescription are important underlying factors. As the first point of contact, the pharmacist has an important role in controlling topical corticosteroid abuse. Aims: This study aimed to evaluate the knowledge, attitudes, and behavior regarding topical corticosteroids in a sample of pharmacy students. Methods: A cross-sectional survey was carried out among pharmacy students using convenience sampling method. A total of 110 questionnaires were distributed, and 103 valid responses were obtained. Results: Majority of the students were conversant of the fact that different classes of topical corticosteroids effectuate different effects. Majority of the students concurred on points such as topical corticosteroids can have significant cutaneous adverse effects, the important role pharmacist plays in preventing topical steroid abuse, and the need to hold fast dispensing of topical corticosteroids on a prescription-only basis. However, a significant gap in knowledge related to specific side effects and awareness of different classes of topical corticosteroids was noted. Moreover, there was no statistical significant difference in terms of knowledge and awareness regarding topical corticosteroid use between postgraduate and undergraduate students. Conclusion: In our study, although several students were aware of the potential adverse effects of topical corticosteroids, there were gaps in the awareness about specific classes and adverse effects. Knowledge regarding the ethical and rational use of topical corticosteroids should be disseminated among pharmacy students, and the dermatologists should play a key role in this.